Analisis Pengaruh Inflasi Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2016 –2020 - Reza Maulana; Nanda Nur Hidayat; Deris Dermawan (Universitas Labuhanbatu, 2022)
Developing countries generally have economic problems such as high inflation rates and slow economic growth. Inflation is an important economic indicator, the rate of growth is always strived to remain low and stable so as not to cause macroeconomic disease which will later have an impact on economic instability. In this regard, there is one thing that requires special vigilance and attention from the government, namely inflation. Various efforts must be made by the government to suppress inflation. Inflation is often caused by an economic crisis. In Indonesia, the monetary crisis begins with the upward depreciation of the rupiah exchange rate against foreign currencies, especially the United States dollar. This has the effect of stifling the price of goods entering Indonesia from abroad. As a result, the price of goods sold domestically also increases. In particular, the Government of Indonesia, Looking at past economic momentum, Indonesia's economic growth based on the rate of Gross Domestic Product in 2018 to 2020 continues to decline, which is influenced by the COVID-19 pandemic, where in 2020 the rate of Gross Domestic Product has decreased drastically by -2 ,50%. The data analysis technique used in this study is quantitative using the SPSS data program.